Energy and Economical Analysis of Drying Process of Domestic Wastewater Treatment Sludge with Heat Pump - Ozan Efe; Ümit Ünver; Selman Cagman (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
In this study, a heat pump was designed to dry the sludge produced by a wastewater treatment plant. The purpose of drying the sludge is to convert it into raw material as fuel pellets, which can provide some or all of the energy needed by the treatment plant. The design of the heat pump considered the plant's production capacity and sludge generation rate. All thermal analyses were carried out according to the First Law of Thermodynamics. The heat pump system performances are investigated by using Danfoss Coolselector 2.0 program. The capacities of the heat pump components were calculated for different refrigerants and performance coefficients. The highest coefficient of performance (CoP) was found to be 5.99 for R1234zeE in summer, while the lowest was 2.33 for R134a. If the sludge is burned as biofuel, theoretically it was estimated that the energy production could range from 723,000 kWh/month to 744,000 kWh/month for the R407c and R1234zeE refrigerants respectively. The economic analysis showed that the system's payback period could range from 1.9 to 6.5 years.